Transcontinental Reflections in the Revised South African History Curriculum on Globalism and National Narratives : (and its Reflection in Grade 12 Textbooks) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The early twenty-first century evidenced a worldwide change in History teaching through the means of several revised History curricula in the further education and training (FET) phase (high schools) and the developments of textbooks as a result of this. In South Africa, these trends have coincided with a period of educational transformation since the African National Congress took over as the leading political party in 1994. After close to 15 years, the transformational outcome also marked a change in the approach to History in the school curriculum and textbooks. This paper is structured to concisely debate globalisation and national narratives as foci in South Africa’s revised History curriculum within current transcontinental reflections in history teaching. The implementation of these aspects in the revised South African History curriculum in the FET phase for specifically the Grade 12 level regarding textbook writing is only shortly discussed, accentuated, and critically analysed.
Keywords: History teaching; revised History curricula; further education and training (FET); educational transformation; globalisation; national narratives; South Africa’s revised History curriculum; transcontinental reflections